Vitamina D em obesos e não obesos: possíveis correlações com adiponectina e resistência à insulina - Marina Carvalho-Rassbach (2017)
Background: Obesity is a major public health problem that affects over 500 million people worldwide. In Brazil, obesity reaches 20.8% of the population. Like obesity, the prevalence of individuals with vitamin D insufficiency is pandemic and there are numerous studies suggesting that the endocrine system, which involves vitamin D, is altered in individuals with obesity. Obesity has been inversely associated with levels of 25-hydroxyvitamin D (25OHD). Some studies have associated 25OHD with low concentrations of the metabolic syndrome, diabetes, and insulin resistance. Insulin resistance has also been associated with low levels of adiponectin. Adiponectin is a plasma protein of 30kDa secreted specifically by adipose tissue. Excess adipose tissue induces a disruption in the production of adipokines, increasing the production of inflammatory and reducing inflammatory ones, like adiponectin. This results in a chronic inflammatory state of the organism and insulin resistance. Plasma levels of adiponectin are reduced in insulin resistant states. Studies have suggested that there is an association between adiponectin, in patients with obesity, and vitamin D insufficiency, with positive feedback after one year of supplementation with vitamin D3. It is not well known the relationship between obesity, vitamin D insufficiency and insulin resistance. The aim of this study is to verify the association between the levels of 25OHD in patients with obesity (body mass index or BMI≥ 30kg/m²) and eutrophic (BMI> 18.5 and 24.9 kg/m²), excluding the range overweight BMI (BMI≥25 to 29.9kg/m²), and adiponectin and insulin resistance. Through a transverse study we evaluated anthropometric indicators, bio impedance levels, 25OHD, adiponectin and insulin resistance by Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) in both groups. The association between vitamin D, adiponectin and HOMA-IR was tested and compared in both groups and in the whole sample by logistic regression. Results: We evaluated 76 patients, 40 with obesity (52,6%), the mean age was 35,0±9,5 years, 75% female, and 65,8% had 25OHD insufficiency. Mean BMI was 22,9±1,5 and 34,4±4,7kg/m2 among eutrophic or obese, respectively. There was no association between 25OHD levels and adiponectin or insulin resistance in obese and eutrophic patients. We only found an inverse association, independent of age and gender, between 25OHD and fat percentage measured by bioelectric impedance (p=0.011, R²= 0.07 and CI of the 0.90 to 0.99) Conclusion: There was no association among vitamin D and the parameters studied for that population. There is still a lot to understand about the association among 25OHD, adiponectin and insulin resistance. The controversy of the theme remains, especially in that sample of the Brazilian population. Studies have showed that ethnic aspects and vitamin D receptor genetic polymorphisms could alter the relations between those variables. Future studies involving larger samples and more skin colors can be useful.